2000
DOI: 10.1152/jappl.2000.89.6.2391
|View full text |Cite
|
Sign up to set email alerts
|

Role of mitogen-activated protein kinases in pulmonary endothelial cells exposed to cyclic strain

Abstract: The aim of this study was to examine the role of mitogen-activated protein kinases (MAPKs) activation in bovine pulmonary arterial endothelial cells (EC) exposed to cyclic strain. EC were subjected to 10% average strain at 60 cycles/min. Cyclic strain induced activation of extracellular signal-regulated kinase (ERK; 1.5-fold), c-Jun NH(2)-terminal protein kinase (JNK; 1.9-fold), and p38 (1. 5-fold) with a peak at 30 min. To investigate the functional role of the activated MAPKs, we analyzed cells after treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
64
1

Year Published

2001
2001
2007
2007

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(69 citation statements)
references
References 31 publications
4
64
1
Order By: Relevance
“…Our finding of stretch-induced phosphorylation of ERK1/2, JNK, and p38 in myometrial SMCs in vitro is consistent with data from endothelial cells (24), vascular SMCs (28), mesangial cells (17), and cardiac myocytes (42). Importantly, our finding that ERK1/2 and p38 phosphorylation are increased in gravid (but not nongravid) myometrium before the onset of labor indicate that our in vitro data are informative of physio- 6.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Our finding of stretch-induced phosphorylation of ERK1/2, JNK, and p38 in myometrial SMCs in vitro is consistent with data from endothelial cells (24), vascular SMCs (28), mesangial cells (17), and cardiac myocytes (42). Importantly, our finding that ERK1/2 and p38 phosphorylation are increased in gravid (but not nongravid) myometrium before the onset of labor indicate that our in vitro data are informative of physio- 6.…”
Section: Discussionsupporting
confidence: 90%
“…Similarly, Kito et al (24) showed that specific inhibitors and dominant negative mutants that target any one MAPK pathway completely abolished stretch-induced AP-1 binding and activity. It is conceivable that activation of all three MAPKs is necessary to properly activate the downstream target, Elk-1, which requires phosphorylation of several residues in the carboxy terminus.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations